Proportion of foot ulcer, knowledge and practice on foot care among diabetic patients in medical college and hospital, Kolkata - Maji, Moumita; Hembrom, Mousumi; Panchadhai, Jayati (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetic foot ulcers (DFU) are one of the most common and devastating complications of diabetes, and affect 15% of all diabetic patients. In this context objective of the study was to find out the proportion of foot ulcers and to assess knowledge and practice regarding foot care among diabetic patients. Methods: Descriptive survey research design was adopted. Samples (204) were selected by systematic random sampling technique at diabetic clinic of Medical College and Hospital, Kolkata. Diabetic patients were interviewed by a semi-structured interview schedule for demographic data and structured interview schedule for knowledge and rating scale for practice were used. Results: The study findings showed that the proportion of foot ulcers was 7.35% among diabetic patients, and 59.31% of patients had average knowledge, and 71.57% had a moderate level of practice regarding foot care. A significant strong relationship was found between knowledge and practice of foot care [r df (202) =0.79*p<0.05], among diabetic parents. The study results also revealed that there was a significant association between the knowledge level with the patient’s residential area, educational status, occupation, monthly income and duration of diabetes and practice of foot care associated with educational status, occupation, and monthly family income. Conclusions: It was concluded that educational programmes focusing on diabetic foot care are necessary to improve foot care practices and prevent foot complications among diabetic patients.